Mamma, tata i papas w łacińskich inskrypcjach chrześcijańskich z Rzymu III-VI wieku - Stawoska-Jundziłł, Bożena (Vox Patrum, 2003)
The article is an analysis of the Christian inscriptions from Roman catacombs (ICUR NS vol. 1-10), which include words: mamma, tata, papas and their derivatives. In comparison to non-Christian inscriptions from CIL, investigated by K.R. Bradley (129 from Rome and 29 from provinces), Christian ones are not numerous, as we have 14 of them and 2 which are doubtful. They originate from the whole period of exhibition of Christian epitaphs in Rome, which lasted from III to VI century. The discussed words most frequently are related to nannies and a man, who looked after infants and little children - the same situation took place in pagan societies. Those people stayed with the families till the end of their lives. Just like in the pagan societies, it has been stated that the tutors had contacts with grown up wards, though the feelings were usually caused by the actions performed not by preceptors them- serves. The inscriptions often does not include the names of those people. Also the tutor have some strong feelings towards the children as they happened to found some epitaphs themselves. Only some of inscriptions may prove using the words discussed in relations to parents. Few inscriptions may indicate the will of resigning of the preceptors’ services and taking the tasks over by children’s parents. That may be also caused by economical problems of the family burying the dead members in the catacombs.